Precious Metals Market Development Trends - Efimov D. S. (Days of Student Science, 2022)
The presented article touches upon the issues of changing rates for precious metals. It is indicated that the prices of precious metals are also unstable, as well as the exchange rate, since they depend on many factors: the state of the economy, world politics, demand for precious metals in industry. The author analyzed the prices for precious metals based on the data of the Central Bank of the Russian Federation, which found that precious metals are constantly growing steadily in price
Keywords: динамика; динамика; драгоценные металлы; драгоценные металлы; рынок драгоценных металлов; рынок драгоценных металлов; цены; Центральный банк РФ; Центральный банк РФ; курс драгоценных металлов